Heavy metal concentrations in drinking water in the region north-east of Jhunjhunu, Rajasthan, India - Kumar, Anil (European Journal of Chemistry, 2023)
Groundwater is contaminated by undesirable elements that are introduced directly or indirectly into a natural water reservoir supplied by human activity, thus changing its physico-chemical properties. The north-east of Jhunjhunu in Rajasthan state of India was chosen as the study area due to the lack of research evidence in the past. The heavy metal content of a total of 42 water samples was analysed using an atomic absorption spectrometer. The copper and iron content in the groundwater of the study area is revealing a spatial distribution range of 1.75 to 4.01 mg/L for copper and 0.44 to 1.22 mg/L for iron. The obtained result was compared with Buero of Indian Standard (10500:2012), Indian Council of Medical Research, and World Health Organisation. There are iron and copper mining facilities in the studied area. Therefore, the concentration of both minerals was observed in the groundwater of all sampling stations. The iron and copper content are much higher in groundwater than the permissible limit of Buero of Indian Standard and World Health Organisation. The manganese content was not detected at all sampling sites. Both iron and copper elements are trace elements, and their higher concentration has proven to be a major problem and there are many health risks associated with it. These observed concentrations indicate a hazardous risk to human health. The official authorities should take the necessary measures in this regard.